2021
DOI: 10.1039/d1cy00550b
|View full text |Cite
|
Sign up to set email alerts
|

Nb2O5 as a radical modulator during oxidative dehydrogenation and as a Lewis acid promoter in CO2 assisted dehydrogenation of octane over confined 2D engineered NiO–Nb2O5–Al2O3

Abstract: Mesoporous 2D NiO-Nb2O5-Al2O3 nanorods (and, for the first time, template free ordered mesoporous alumina (OMA)) were prepared via glycol-thermal synthesis for the direct transformation of octane to octenes via CO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Ceria (as support) with different morphologies, was prepared using the hydro-thermal and glycol-thermal methods. 22 , 23 , 24 , 25 In the naming applied for these catalysts, LS, NS, MM, NR, and NC refer to catalysts containing ceria with large sphere, nanosphere, mixed morphology, nanorods, and nanocube morphologies, respectively. The ceria with different morphologies is in the form of the fluorite phase with a face-centered cubic Bravais lattice (fcc).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceria (as support) with different morphologies, was prepared using the hydro-thermal and glycol-thermal methods. 22 , 23 , 24 , 25 In the naming applied for these catalysts, LS, NS, MM, NR, and NC refer to catalysts containing ceria with large sphere, nanosphere, mixed morphology, nanorods, and nanocube morphologies, respectively. The ceria with different morphologies is in the form of the fluorite phase with a face-centered cubic Bravais lattice (fcc).…”
Section: Resultsmentioning
confidence: 99%
“…As evidenced by the EDX line scan of Pt-V/CeO 2 (MM) shown in Figure 3 , close proximity of Pt and V sites exists for these catalysts. Interestingly, the nanospheres within the Pt-V/CeO 2 (NS) catalyst, prepared via a new modified glycol-thermal method, 22 is composed of a grouping of several thermally stable unsupported quantum dot (QD) ceria units which are known to have extraordinary properties (particle size distribution is provided in Figure S2 ). 27 , 28 Having nanospheres made of QD ceria resulted in a high surface area of 107 m 2 /g for this catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…These exciting results are likely due to the reduction of CuO sites (using heat and H 2 ) at 200°C and the well-known RWGS (or great WGS) activity of Fe 2 O 3 . 37,38 Having this synergistic bifunctionality activated by either thermal or plasma (as energy sources) likely resulted in a high yield toward methanol in this study.…”
Section: Cu-based Catalystsmentioning
confidence: 89%
“…They characterized the spent supported catalysts from this application and suggested that the active sites for methanol formation are in situ formed mixed NiO with metal support interactions with the Fe 2 O 3 and NiFe 2 O 4 spinel with both hydrogenating and RWGS ability. 38,40,41 3). 32,40,42 CoO x /MgO and Al 2 O 3 were used as catalysts for CO 2 hydrogenation to methanol.…”
Section: Ni-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation